Characteristics Of Mathematics Lesson Valued As Effective By Excellent Teachers And Their Pupils - Tan, Saw Fen (2012)
This study aimed to answer four research questions: (1) What are the characteristics of mathematics lesson valued as effective by the primary school Excellent Teachers? (ii) What are the characteristics of mathematics lesson that are valued as effective by the pupils? (3) What are the similarities or differences between the Excellent Teachers’ and pupils’ perceptions of effective mathematics lesson? and (iv) What are the similarities or differences between characteristics of mathematics lesson valued as effective by the pupils with different academic performance? The research was conducted using a case study design.